Significance of Meconium Stained Amniotic Fluid in Relation To Fetal Outcome (Journal of Fatima Jinnah Medical University, 2018)
Introduction: The presence of meconium stained amniotic fluid is a matter of great concern for both Obstetricians and Neonatologists due to increased perinatal morbidity and mortality associated with meconium staining and aspiration. The normal amniotic fluid is clear and staining of amniotic fluid is of prognostic value in the process of labour. Meconium staining has to be dealt with great caution with continuous fetomaternal monitoring and timely intervention, but still with all measures we are not sure of a healthy outcome. Objectives: Determine the correlation of meconium stained liquor with fetal outcome. Study Design: Cross-sectional descriptive study. Setting: The study was carried in the Department of Obstetrics and Gynaecology, Unit-I, Services Hospital, Lahore. Duration of Study with Dates: Study was conducted over a period of six months from 24-08-2006 to 2302-2007. Subjects and Methods: The study was conducted on 150 cases of pregnant women in labour, with meconium staining of the amniotic fluid. Results: Mean age was found to be 25.14±3.91 years. Considering Apgar score at 1 minute, 82 infants (54.7%) had score between 0-4 and in 68 infants (45.3%) it was 5-6. Apgar score was 6-7 at 5 minutes in 95 infants (63.3%) and in 53 (35.4%) it was 8-9. It was 0-5 in 2 cases (1.3%). Considering the need for resuscitation, 111 infants (74%) required resuscitation and in 39 (26%) it was not needed. 86 infants (57.6%) were stable and 64 infants (42.7%) required admission to neonatal unit. 60 infants (95.2%) had 1-5 days stay in NNU and in 3 cases (4.8%) the stay was for 6-10 days. Conclusion: There is a relation between the presence of meconium stained amniotic fluid and the Apgar score, both determining the neonatal morbidity interms of need for neonatal resuscitation, active oropharyngeal suction, need of NNU admission for artificial ventilation or extracorporeal oxygen. So in labouring patients careful monitoring should be done regarding : fetal heart rate, its patterns and colour of liquor ( if meconium _stained, then grade of meconium ), so as to intervene timely and hence avoiding the neonatal morbidity
Keywords: Meconium Stained Amniotic Fluid, IUGR, Apgar score.